The demand for health insurance in a poor economy: Evidence from Burkina Faso - Michael Schleicher; Stefan Klonner; Rainer Sauerborn; Alie Sié; Aurélia Souares-Coutant (University of Heidelberg, Department of Economics, 2018)
We investigate the properties of health insurance demand in Burkina Faso, where we offered poor households a voluntary health insurance product at half the usual price. The targeting procedure we implemented delivers a fuzzy regression discontinuity design, which identifies the price elasticity of demand for health insurance as well as associated selection effects. We find large price elasticities among urban households, whereas the demand of rural households is price-inelastic. There are important selection effects, with widowed male household heads being most price-sensitive. Correlating these heterogeneous effects with survey data on informal transfers and health expenditures, our results suggest that informal risk-sharing largely crowds out formal insurance and that a single insurance product may fail to align with poor households' small health budgets. We find no adverse selection into health insurance.
urn:nbn:de:bsz:16-heidok-245317
Keywords: G22; I13; I38; O15; 330; Health insurance; Micro-health insurance; Social health insurance; Health insurance demand; Targeting; Adverse selection